2021
DOI: 10.3390/ijerph18168858
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reduced Physical Activity on the Lipid Profile in Patients with High Cardiovascular Risk during COVID-19 Lockdown

Abstract: Background: The COVID-19 pandemic is a serious global health problem. In Italy, to limit the infections, the government ordered lockdown from March 2020. This measure, designed to contain the virus, led to serious limitations on the daily life of the individuals it affected, and in particular in the limitation of physical exercise. The aim of this study was to evaluate the effects of reduced physical activity on the lipid profile in patients with high cardiovascular risk. Methods: We enrolled 38 dyslipidemic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
1
23
0
2
Order By: Relevance
“…We believe the significant correlation between the IPAQ and peak VO 2 /Kg observed in our study to be an important result because self-reported methods of assessment such as the IPAQ are cheap and can be easily incorporated into routine clinical practice [52][53][54][55][56][57] allowing us to obtain additional data about the regular lives of rToF patients. The integration of the data obtained from CPET with the real level of physical activity of these patients based on their IPAQ score could allow us to better understand the clinical status of rToF patients, highlighting even small initial decreases in myocardial reserve in apparently asymptomatic patients.…”
Section: Usefulness Of the Ipaq Survey In Rtof Patientsmentioning
confidence: 73%
“…We believe the significant correlation between the IPAQ and peak VO 2 /Kg observed in our study to be an important result because self-reported methods of assessment such as the IPAQ are cheap and can be easily incorporated into routine clinical practice [52][53][54][55][56][57] allowing us to obtain additional data about the regular lives of rToF patients. The integration of the data obtained from CPET with the real level of physical activity of these patients based on their IPAQ score could allow us to better understand the clinical status of rToF patients, highlighting even small initial decreases in myocardial reserve in apparently asymptomatic patients.…”
Section: Usefulness Of the Ipaq Survey In Rtof Patientsmentioning
confidence: 73%
“…On the one hand, it could be an indication of relaxation and attention to a healthier diet; on the other, if correlated with reduced physical activity and increased laziness, it could contribute to weight gain and consequently to health risks such as cardiovascular diseases, metabolic risk, cancer, etc. [ 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of resistance training have been demonstrated on body composition, the cardiovascular system, glucose metabolism, dyslipidemia, quality of life and sarcopenia [ 28 , 29 , 30 , 31 ]. Marzolini et al [ 32 ] compared aerobic training alone versus aerobic plus resistance training, demonstrating that combined training was more effective on body composition, strength, and some indicators of cardiovascular fitness.…”
Section: Discussionmentioning
confidence: 99%